Efforts to Increase Organizational Commitment Through Visionary Leadership, Learning Organizations, and Competencies - Andari, Andari; Setiawan, Heru; Affandi, Azhar (Almana : Jurnal Manajemen dan Bisnis, 2024)
With quality education, the quality of a nation will be reflected. To produce superior human resources, lecturers as educators have a responsibility to improve human resources by providing quality education. In achieving the vision and mission of higher education, it is necessary to support the organizational commitment of lecturers. The purpose of the study analyze efforts to increase organizational commitment through visionary leadership, learning organizations, and competencies. The method used in this study is quantitative, using the Structural Equation Model (SEM) analysis tool. The population of permanent lecturers of the Foundation amounted to 3322 people, and the sample amounted to 357 respondents. Sample determination using stratified cluster random sampling. The results of this study explain that visionary leadership, learning organizations, and competencies partially affect organizational commitment. In addition, the results of the hypothesis test simultaneously show visionary leadership, learning organizations and competencies together affect organizational commitment. To increase organizational commitment, Private Universities in the Banten Province area need continuous improvement, including increasing the effectiveness of Visionary leadership, the existence of institutions to continue to learn and adapt as ideal Learning Organizations, and increasing their Competencies its lecturers, as an effort to build and increase the organizational commitment of the Dosen.